A Possible Future Return to the Past. (March 2017) - Rios, Josh
Abstract : This text treats a specific Doctor Who storyline, The Aztecs (1964), as a catalyst for questioning Enlightenment-era notions of rationality, progress, and technologic advancement in relation to colonial constructions of non-European societies as static and futureless. Moreover, it looks at the role geography and travel (including time travel) have played in reifying Modernity as a series of traceable, enclosed steps leading from the primitive to the contemporary. To this end, postcolonial speculative fiction is formulated as a testing ground to interrogate past and current modes of imperialism, as well as explore various alternative pasts and futurities. Clearly, reconfigurations of erased histories and ethnic traumas are necessary to formulate counter-narratives against colonialist logics of repression; however, recuperative projects also need to be undertaken with the utmost criticality and self-reflexivity. The fiction of Chicanx cyberpunk writer Ernest Hogan serves to expose the fraught nature of reclaiming pre-colonial or Indigenous pasts. Lastly, this text supposes that representation and cultural constructions have real effects in the world. As such, symbols are never merely symbolic; they aid in the creation of both justifications for marginalization as well as powerful correctives capable of transforming our social spheres and social lives in potent ways.